Q: What is the answer for this 5x plus 2 plus 3x?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

The answer to the equation 5x - 3x + 2 = 1 is -0.5.

-5x^2 - 55x - 120

5x - 10 = 3x + 2 5x - 3x = 2 + 10 2x = 12 x = 12/2 x = 6

(3x - 5x) + (x2 - 6x2) = -2x -5x2 = -x(2 + 5x)

It is the same as 8x+2 when simplified

Related questions

The answer to the equation 5x - 3x + 2 = 1 is -0.5.

2(3x + 4) + 5x - 2

-5x^2 - 55x - 120

5x+2 = 3x-6 5x-3x = -6-2 2x = -8 x = -4

3x2 + 5x + 2 is a quadratic expression that can be factored as follows: 3x2 + 5x + 2 = 3x2 + 3x + 2x + 2 = 3x(x + 1) + 2(x + 1) = (3x + 2)(x + 1)

5x - 10 = 3x + 2 5x - 3x = 2 + 10 2x = 12 x = 12/2 x = 6

8x

3x+2 = 5x so 2x = 2 and hence x = 2/2 = 1

(3x - 5x) + (x2 - 6x2) = -2x -5x2 = -x(2 + 5x)

3x + 5x = 2x + 28x = 2x + 26x = 2x = (2/6) = 1/3

6-3x = 5x-10x+10 6-3x = -5x+10 -3x+5x = 10-6 2x = 4 x = 2

It is the same as 8x+2 when simplified